Computer literacy in Utan Aji: a case study of students from Sekolah Menengah Kebangsaan Syed Ahmad and Sekolah Menengah Kebangsaan Syed Alwi - Khauthar Ismail (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2011)
The major objective of this research is to find out the different levels of computer literacy among male and female teenagers in Utan Aji, Perlis, Malaysia. The methods used in this research were survey and field observation. In this research, three independent variables were tested, namely, gender, location and socio-economic factors. The result shows that the two most influential factors are gender and socioeconomic.The study proofs that gender variables such as lack of confidence, inferiority complex and gender stereotypes are the factors affecting digital divide among male and female respondents. However, the gender stereotype among respondents is only limited to the level of expertise among genders and not on the treatment in the ICTL class. In addition, gender also contributed to the different levels of computer usage. In fact, the study discovers that location and area of the respondents' houses do not contribute to the digital divide. However, the location and condition of the cyber café do contribute to the digital divide among the respondents. Meanwhile in the socio-economic variables; the amount of the family's income and the parents' educational background do contribute to the different levels of computer literacy. Family's income is important in measuring the affordability to have a computer and subscribing to the Internet. Meanwhile, parents' educational level is important in measuring the perception parents' on the usage of computer. The levels of parents' education is related